Avaliaç\~ao dos cursos de graduaç\~ao no Brasil: Consideraç\~oes sobre o sinaes e seu futuro - Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Since 2004, a complex high-stake assessment of the federal higher education system has been in operation in Brazil. Established by law, the National Higher Education Assessment System (Sistema Nacional de Avaliaç\~ao da Educaç\~ao Superior - Sinaes) consists of three components: the evaluation of student performance, the evaluation of programmes and the evaluation of educational institutions. This work makes a critical analysis of the quality indicators that guide such evaluation processes and regulate the accreditation of higher education providers and programmes. Based on this analysis, reforms are proposed focused on the programme evaluation component. The immediate objective is to make it more complete, simpler to understand, cheaper to run and more suited to contemporary trends. The ultimate goal can be either to ensure quality or to establish regulatory criteria - or both. The proposed reforms can also help mapping trends on inclusion and diversity on campuses, in addition to provide society with relevant information about the higher education system. The main recommendation is the discontinuation of the National Student Performance Examination (Exame Nacional de Desempenho dos Estudantes - Enade), and the replacement of the quality indicators currently based fundamentally on Enade results by a set of indicators based essentially on information extractable from administrative records existing in Brazil. The indicators presented are merely illustrative, but seek to cover four dimensions: efficiency, efficacy, effectiveness, and equity. It is argued that, at best, contributions made in the past by Sinaes are already insufficient to assess the federal higher education system. Restructuring it is necessary and a new evaluation system that is more advanced, cheaper, and effective can be designed to adequately replace Sinaes.
Keywords: I21; I23; I28; 330; higher education; large-scale assessment; regulation; Brazil; Sinaes; indicators; administrative records